Playing with Identity Politics: An Analysis Post-2019 Presidential Election - Aditya Candra Lesmana; Budi Sutrisno (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2021)
This article aims to discuss the potential for the disintegration of the Indonesian nation after the 2019 general election. The method used is a literature study using the concept of Identity Politics. The result of the study found that the game of identity politics in the implementation of the Presidential election created a counter-productive process. There is a potential for national disintegration due to the identity politics played by the two pairs of candidates fighting in the Presidential election. The strengthening of feelings of in-groupness creates dislike for other groups pushed the emergence of various phenomena and acts of violence due to the use of identity politics in the 2019 presidential election.AbstrakArtikel ini bertujuan untuk membahas potensi disintegrasi bangsa Indonesia pasca pemilu 2019. Metode yang digunakan adalah studi kepustakaan dengan menggunakan konsep identitas politik. Hasil penelitian menemukan bahwa permainan politik identitas dalam pelaksanaan Pilpres menciptakan proses yang kontra produktif. Ada potensi disintegrasi bangsa akibat politik identitas yang dimainkan dua pasangan calon yang bertarung di Pilpres. Menguatnya perasaan in-groupness menimbulkan ketidaksukaan terhadap kelompok lain mendorong munculnya berbagai fenomena dan tindakan kekerasan akibat penggunaan politik identitas pada pemilihan presiden 2019.